ANALISIS DAMPAK PENGANGURAN TERBUKA TERHADAP JUMLAH KEMISKINAN DI KOTA MEDAN - Rezeki Ramadhan , Rizky; Haniah Putri , Shalwa; Syahputri , Mira; Alya Putri , Wanti; Khairunisa , Khairunisa; Dwi Septiani , Citra (PT. ANAN PUBLISHER CENDEKIA, 2024)
Unemployment, specifically among recent graduates, is a prevalent phenomenon in society. It is characterized by individuals possessing adequate qualifications but not engaged in employment-seeking activities. This issue has significant implications for poverty, defined as the condition wherein individuals or households face difficulties in fulfilling basic needs.This research aims to analyze the impact of open unemployment on the poverty rate in Medan City. The data utilized in this study is derived from secondary sources obtained from relevant authorities, specifically the North Sumatra Central Statistics Agency, spanning the years 2017 to 2022. The analytical approach employed in this study is the simple linear regression technique.The results of data analysis reveal that open unemployment in Medan City has a discernible influence on the poverty rate within the city, demonstrating a 1.01% impact during the period from 2017 to 2022.